PENGARUH BEBAN KERJA, DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP TURNOVER INTENTION KARYAWAN DI TIDAR PROPERTY GROUP MALANG - Elok Hermawati; Ike Kusdyah R; Tin Agustina K (Journal of Applied Management Studies, 2021)
Turnover is a problem that should be considered by the company, because the impact is quite large for the company. The impact is in the form of increasing employees who think about leaving the company, lowering the company's image, feeling the pressure of the workload and an uncomfortable work environment for employees. The same thing was felt by employees at Tidar Property Group Malang. In this regard, this study aims to determine how the influence of workload, work discipline and work environment on turnover intention at Tidar Property Group Malang. The samples taken were all employees of Tidar Property Group Malang as many as 68 staff employees who were used for this research, using saturated sampling technique and using the rank and file level system / grade level.Data analysis carried out in this study was multiple linear regression analysis using the IBM SPSS 25 program. This study was a survey research using a questionnaire. The results of this study indicate that partially, there is a positive and significant influence between the workload variable on turnover intention, a negative and insignificant effect of work discipline on turnover intention, and a positive and significant effect of the work environment on turnover intention. It is also known that the variables of workload, work discipline and work environment affect turnover intention at Tidar Property Group Malang.